A Simple Process to Prepare High‐Efficiency Durable Oil–Water Filter (Adv. Mater. Interfaces 17/2021). Issue 17 (12th September 2021) - Hu, Jiawei; Chen, Yi; Zhou, Yueyun; Fan, Xiaokun; Li, Jie; Li, Zhihan; Cai, Rong; Zeng, Guangsheng; Liu, Wenyong
Abstract : High‐Efficiency Oil–Water Filter In article number 2100594, Jiawei Hu, Yi Chen, and co‐workers prepare a high‐efficiency oil–water filter by coating sodium alginate hydrogel layer in the surface of porous sand core. This filter exhibits excellent separation ability toward oil–water mixed liquor and oil–water emulsion. Moreover, it has excellent chemical stability, easy cleanliness, and strong durability. All these characteristics make this filter a potential candidate for large‐scale applications in wastewater treatment.